Feasible laser parameters in fabrication of MEMS structures on silicon - Yong, Chee Ping (2010)
The technique of making MEMS structures are kept improving which from old fashion with high cost machine to very advanced one to save time and labor cost. In this report, laser machining of silicon using ND:YAG is introduced. The main objectives are generating MEMS structures on silicon wafer by using laser micromachining and the effects of parameters of laser micromachining on silicon.STATISTICA is used to design and analyze the experiments. Two experimental sets: (1) laser processing with assist gas and (2)laser processing without assist gas were carried out. Basic feature of MEMS and micro spots were generated. The micro features were investigated under SEM. Experimental results were analyzed in STATISTICA. Analyzed results show that laser power is the most significant effect followed by pulse width and the assist gas on the micro feature size and particularly feature quality. It was found that laser processing without assist gas produce promising results.